Evaluating Lexicon Weighting and Machine Learning Models for Sentiment Classification of Indonesian Mangrove Ecotourism Reviews - Chahyadi, Ferdi; Uperiati, Alena; Pratiwi , Risdy Absari Indah; Hamid, Nur (Jurnal Teknik Informatika (Jutif), 2025)
Sentiment analysis on ecotourism reviews presents specific challenges due to descriptive writing styles, the use of ambiguous words, and contextual meaning shifts (contextual polarity shift). These characteristics often cause lexicon-based approaches to produce unstable polarity labels. This study aims to evaluate the influence of two lexicon weighting methods, namely Mean Weighting and Summation Weighting, on the initial sentiment labeling of mangrove ecotourism reviews and to assess the performance of machine learning models trained using these labels. The research method includes text preprocessing, lexicon-based scoring using the InSet lexicon, feature extraction with Term Frequency–Inverse Document Frequency (TF–IDF), and the training of two classification algorithms, Support Vector Machine (SVM) and Logistic Regression (LR). The results show that the Mean Weighting method produces more stable polarity scores and higher model performance. The combination of SVM with Mean Weighting achieves the best results with an accuracy of 0.902, macro precision of 0.876, macro recall of 0.819, a macro F1-score of 0.841, and a weighted F1-score of 0.899. Meanwhile, LR with Mean Weighting reaches an accuracy of 0.891 with a similar performance pattern. In contrast, the Summation Weighting method results in lower performance for both algorithms. Error analysis indicates that neutral sentences and ambiguous words such as “bagus” and “ramai” frequently lead to misclassification. These findings highlight that the choice of lexicon weighting method plays a crucial role in improving sentiment classification accuracy and contributes to the development of hybrid approaches in text mining and sentiment analysis for the Indonesian language.